The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1159/000088903
|View full text |Cite
|
Sign up to set email alerts
|

Acid Susceptibility at Various Depths of pH-Cycled Enamel and Dentine Specimens

Abstract: pH-cycling and in situ studies have shown that fluctuations in de-/remineralisation conditions or in fluoride usage can lead to laminations inside enamel or dentine lesions. Layers with different mineral content are thought to reflect the history of fluoride administrations. Studying the dissolution properties of such lesions at various depths – using bulk specimens – is presumably hampered by limited diffusion of acids through the lesion pores. Therefore, in this study the acid susceptibility of enamel and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
1
17
0
3
Order By: Relevance
“…Previous studies had indicated full remineralization was unable to achieve even with high concentration of fluoride. 26 Our shortterm experiment showed GCE and gallic acid had combined effects with fluoride, but the mechanism was still unknown. More studies were needed to investigate whether G. chinensis could promote the effect of fluoride or they could enhance remineralization separately without inhabitations.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies had indicated full remineralization was unable to achieve even with high concentration of fluoride. 26 Our shortterm experiment showed GCE and gallic acid had combined effects with fluoride, but the mechanism was still unknown. More studies were needed to investigate whether G. chinensis could promote the effect of fluoride or they could enhance remineralization separately without inhabitations.…”
Section: Discussionmentioning
confidence: 84%
“…The pH-cycling model chosen for enamel and dentin was based on previous studies each focusing on one type of dental substrate (3,21,22). The models should be able to simulate the demineralizing and remineralizing episodes, considering the composition of the different dental substrates, in order to create a subsurface mineral loss and not an erosive lesion (10 µm deep) at the end of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the evidence of an increasing prevalence of dental fluorosis (2) and some fluoride limitations, such as the inability to completely remineralize carious lesion (2,3), have led to the search for alternative non-fluoride agents that could provide a complete prevention or arrest of dental caries lesion (4).…”
Section: Introductionmentioning
confidence: 99%
“…18 Among all the models, pH-cycling system is the most popular which mimics the periodic exposure of enamel and dentine to de-/remineralization conditions and to fluoride. 19 In the present study, we followed the regime proposed by Lynch in 2002. 16 Bovine enamel was used because it was easy to obtain and provided a less variable response to both cariogenic challenge and anti-caries treatments comparing with human teeth.…”
Section: Discussionmentioning
confidence: 99%